Response of infrared thermography related parameters to (non-)sport specific exercise and relationship with internal load parameters in individual and team sport athletes—a systematic review - Masur, Lukas; Brand, Florian; Düking, Peter (Frontiers in Sports and Active Living, 2024)
Introduction: Monitoring internal load is crucial for athletes but often requires invasive methods for muscle-related parameters, limiting practicality. Infrared thermography (IRT) related parameters might overcome this limitation. This systematic review aimed to examine the available literature on the response of IRT related parameters to (non-)sport specific exercise and reveal relationships with internal load parameters in athletic populations. Methods: Four scientific databases were systematically searched (February 2024) with keywords related to IRT, load, and sports disciplines. Risk of bias was evaluated using QUADAS-2. Main inclusion criteria for studies were i) reporting of IRT related parameters and other internal load parameters prior/post (non-)sport specific exercise ii) inclusion of least Tier 2 athletes ≥ 18 years. After identifying n = 10538 studies, 13 articles (n = 231 participants) were included.Results: Following (non-)sport specific exercise in athletic populations, the majority of relevant studies showed a decrease in IRT related parameters within 15 minutes, while studies showed an increase in IRT related parameters following 30 minutes, 24 hours, 48 hours, and 72 hours after exercise cessation. Relationships between alterations in IRT related parameters and other internal load parameters are inconsistent across the literature.While the majority of studies show an increase in IRT related parameters following (non-)sport specific exercise, relationships with other internal load parameters and underlying physiological mechanisms evoking IRT related alterations are not conclusively revealed in athletic populations. Future research needs to assess the relationship of IRT related parameters especially with inflammatory parameters in athletic populations following (non-)sport specific exercise. Practitioners might assess IRT related parameters in conjunction with other load parameters.